2014
DOI: 10.1111/joim.12294
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin‐3 level at admission is a strong predictor of short‐term mortality in a community‐based hospital setting

Abstract: Abstract. Bastrup-Birk S, Munthe-Fog L, Skjoedt M-O, Ma YJ, Nielsen H, Køber L, Nielsen OW, Iversen K, Garred P (Rigshospitalet, Copenhagen; Frederiksberg Hospital, Copenhagen; and Bispebjerg Hospital, Copenhagen University Hospitals, Copenhagen, Denmark). Pentraxin-3 level at admission is a strong predictor of shortterm mortality in a community-based hospital setting. J Intern Med 2015; 277: 562-572.Background. The pattern recognition molecule pentraxin-3 (PTX3) is a novel potential marker of prognosis, as el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 45 publications
2
24
1
Order By: Relevance
“…29,30 It has been shown to be beneficial as a marker for many diseases like cardiovascular disease, malignancies, and some specific infections. [31][32][33][34][35] Adult studies have shown serum levels increase with sepsis and septic shock. 36,37 A study of a newborn patient group including premature babies compared the pentraxin 3 values of mothers and babies with early membrane rupture with neonatal results and found it was associated with intraventricular hemorrhage and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 It has been shown to be beneficial as a marker for many diseases like cardiovascular disease, malignancies, and some specific infections. [31][32][33][34][35] Adult studies have shown serum levels increase with sepsis and septic shock. 36,37 A study of a newborn patient group including premature babies compared the pentraxin 3 values of mothers and babies with early membrane rupture with neonatal results and found it was associated with intraventricular hemorrhage and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that the standard blood panel have only limited predictive power in risk assessment when added to physiological parameters [ 26 ], future studies can reveal whether prognostic information can be significantly improved using a whole panel of new and old inflammatory biomarkers. Several biomarkers have shown prognostic strength, for example C-reactive protein, suPAR, YKL-40, Pentraxin-3, Copeptin and Troponin T [ 11 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several old and new biomarkers are useful to estimate short term prognosis [ 11 16 ] and a recent theoretical study has suggested that the use of biomarkers would substantially strengthen the existing triage algorithms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary pro‐inflammatory signals (bacterial components, pathogen‐associated molecular patterns, damage‐associated molecular patterns, IL‐1, TNF‐alpha) induce the synthesis and release of PTX3 in various cell types such as endothelial cells, polymorphonuclear leucocytes (PMN) and monocytes/macrophages . On account of its specific involvement in the immune system and inflammatory processes, and as it can be measured in blood, PTX3 has been characterized as a biomarker of disease severity and outcomes in different cardiovascular diseases, malignancies and specific infections . Since the first report , several studies have focused on the roles of elevated circulating PTX3 in sepsis and related complications such as shock.…”
Section: Introductionmentioning
confidence: 99%